Risk Management: Maintaining Strategic Performance of Start-Up Companies in The Digital Economy Era - Winarno, Budi; Hendarti, Yanita (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to reveal the importance of risk management in strategic performance in start-up companies. This research examines the actual problem of uncertainty in startup companies today. The approach used in this research is a qualitative approach, while the type of research used is library research. The results of this study include that founders of start-up companies must be able to understand risk management, so that they can anticipate various challenges and obstacles that may occur in the future. This is very important because strategic performance can be consistently maintained if the founders of start-up companies understand risk management. Moreover, now is the era of the digital economy which demands rapid adaptation of everything.